Transcriptomic Analysis Identified ARHGAP Family as a Novel Biomarker Associated With Tumor-Promoting Immune Infiltration and Nanomechanical Characteristics in Bladder Cancer - Yang, Chen; Wu, Siqi; Mou, Zezhong; Zhou, Quan; Zhang, Zheyu; Chen, Yiling; Ou, Yuxi; Chen, Xinan; Dai, Xiyu; Xu, Chenyang; Liu, Na; Jiang, Haowen (Frontiers in Cell and Developmental Biology, 2021)
Bladder cancer serves as a common and lethal urinary malignancy worldwide. The role of ARHGAP family gene in BCa and its association with immuno-microenvironment largely remains unknown. ARHGAP family expression and immune infiltration in BCa were analyzed by bioinformatics analysis. Then, we investigated cell proliferation, invasion and migration in vivo and in vitro of ARHGAP family. Furthermore, Atomic force microscopy (AFM) was employed in measuring cellular mechanical properties of BCa cells. According to the results, ARHGAP family genes correlates with a tumor promoting microenvironment with a lower Th1/Th2 cell ratio, higher DC cell infiltration, higher Treg cells infiltration and T cell exhaustion phenotype. Silencing ARHGAP5, ARHGAP17 and ARHGAP24 suppressed BC cell proliferation, migration and metastasis. T24-shARHGAP cells possess relative high Young’s modulus and low adhesive force and cell height. Taken together, ARHGAP family genes promote BC progressing through establishing a tumor promoting microenvironment and promote cancer progression.